Écrire la langue berbère au royaume de Mohamed VI - Stéphanie Pouessel (Revue des Mondes Musulmans et de la Méditerranée)
Never recognized as official languages, the Berber languages have borrowed their written scripts according to the various political systems and cultures they came in contact with. This paper explores the different scripts that have been used to write the Berber languages and tries to search for their underlying intellectual and political filiations. The appropriation of the Latin script, the acquisition or abandonment of the Arabic script stand out as landmarks in the history of these languages, often perceived as one language. Today in Morocco, the Berber identity claim - known as amazigh - tends to cut itself from the Muslim heritage by adopting a specific Berber script conceptualized as indigenous and pre-Islamic. By doing so, this movement refuses the ethnicization of Islam, i.e. its monopolization by one culture and one language: Arabic. This cultural choice is primarily a political stand : the opposition toward the presence of Islam through state policies and instiututions and the wish to restore cultural diversity denied by the post-colonial national construction. This new set-up allows the inscription of amazigh in the Libyc and African areas as well as in the Tamazgha territories (i.e. the whole Berber-speaking areas).